Xport-A functions as a chaperone by stabilizing the first five transmembrane domains of rhodopsin-1 - Catarina J. Gaspar; Tiago Gomes; Joana C. Martins; Manuel N. Melo; Colin Adrain; Tiago N. Cordeiro; Pedro M. Domingos (iScience, 2023)
Summary: Rhodopsin-1 (Rh1), the main photosensitive protein of Drosophila, is a seven-transmembrane domain protein, which is inserted co-translationally in the endoplasmic reticulum (ER) membrane. Biogenesis of Rh1 occurs in the ER, where various chaperones interact with Rh1 to aid in its folding and subsequent transport from the ER to the rhabdomere, the light-sensing organelle of the photoreceptors. Xport-A has been proposed as a chaperone/transport factor for Rh1, but the exact molecular mechanism for Xport-A activity upon Rh1 is unknown. Here, we propose a model where Xport-A functions as a chaperone during the biogenesis of Rh1 in the ER by stabilizing the first five transmembrane domains (TMDs) of Rh1.